Intimate Partner Violence against Women : Prevalence, Formal Reporting, and Risk Factors in Chile - Saavedra, Trinidad; Contreras-Urbina, Manuel; Inchauste, Gabriela (World Bank, Washington, DC, 2022)
Intimate partner violence is among the most common forms of violence against women. In Chile, one in four women who have been in a partner relationship report having experienced some type of partner violence in the past 12 months, whether psychological, physical, sexual, or economic. However, only 22 percent of female victims of intimate partner violence file a formal complaint. This study analyzes the factors that determine the likelihood that a woman will be subject to violence perpetrated by her partner or ex-partner and the factors that determine the probability of reporting the abuse. Individual factors that increase women’s risk of experiencing intimate partner violence include being young, having fewer years of education, having a disability, and having been a victim of sexual abuse in childhood. Other factors include characteristics of partners or ex-partners associated with aggressive behavior in public spaces, having been a victim of intrafamily violence in childhood, and frequent alcohol consumption. The household dynamics that prevent women from participating in economic decision-making and the widespread acceptance of inequitable gender norms also significantly increase the risk that a woman will experience intimate partner violence. The likelihood that a woman will formally report intimate partner violence is mainly determined by the frequency of the episodes, characteristics of the partners or ex-partners, economic empowerment, and whether she has support networks.